Functional Properties and Molecular Architecture of Leukotriene A4 Hydrolase, a Pivotal Catalyst of Chemotactic Leukotriene Formation - Haeggström, Jesper Z. (ScientificWorldJournal, 2002)
The leukotrienes are a family of lipid mediators involved in inflammation and allergy. Leukotriene B(4) is a classical chemoattractant, which triggers adherence and aggregation of leukocytes to the endothelium at only nM concentrations. In addition, leukotriene B(4) modulates immune responses, participates in the host defense against infections, and is a key mediator of PAF-induced lethal shock. Because of these powerful biological effects, leukotriene B4 is implicated in a variety of acute and chronic inflammatory diseases, e.g., nephritis, arthritis, dermatitis, and chronic obstructive pulmonary disease. The final step in the biosynthesis of leukotriene B(4) is catalyzed by leukotriene A(4) hydrolase, a unique bifunctional zinc metalloenzyme with an anion-dependent aminopeptidase activity. Here we describe the most recent developments regarding our understanding of the function and molecular architecture of leukotriene A(4) hydrolase.